Malignant Transformation of Pulmonary Benign Metastasizing Leiomyoma - Song, Kyung Sub (Korean J Thorac Cardiovasc Surg, 2017)
Pulmonary benign metastasizing leiomyoma (PBML) is defined as metastasis of a leiomyoma to lung tissue. It was first reported in 1937. P BML is known as a benign disease, but can undergo malignant transformation. Only 1 case of the malignant transformation of PBML to leiomyosarcoma has been reported previously. In this report, we present a case of malignant transformation of PBML.